Slides to Philosophy 167: Class 11 -- Other Developments in Astronomy from 1642 to 1684 -- Part 2. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Generally corresponds to the video segment: Class 11, Part 2.